2012
DOI: 10.1088/0031-9155/57/10/3177
|View full text |Cite
|
Sign up to set email alerts
|

MagnetoHemoDynamics in the aorta and electrocardiograms

Abstract: This paper addresses a complex multi-physical phenomenon involving cardiac electrophysiology and hemodynamics. The purpose is to model and simulate a phenomenon that has been observed in magnetic resonance imaging machines: in the presence of a strong magnetic field, the T-wave of the electrocardiogram (ECG) gets bigger, which may perturb ECG-gated imaging. This is due to a magnetohydrodynamic (MHD) effect occurring in the aorta. We reproduce this experimental observation through computer simulations on a real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…However other contributions should be considered for complete simulation of the MHD phenomenon. Even if the linear relation between the extracted MHD and the INRIA’s model is slighthly better than between the extracted MHD and the proposed model , it has been shown that the proposed method reflects more adequately the reality that the simplified equation proposed by Martin et al (2012). Applying SVD to the extracted MHD clearly shows that this effect is more complex than a simple eigenvector as suggested by Martin et al (2012).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However other contributions should be considered for complete simulation of the MHD phenomenon. Even if the linear relation between the extracted MHD and the INRIA’s model is slighthly better than between the extracted MHD and the proposed model , it has been shown that the proposed method reflects more adequately the reality that the simplified equation proposed by Martin et al (2012). Applying SVD to the extracted MHD clearly shows that this effect is more complex than a simple eigenvector as suggested by Martin et al (2012).…”
Section: Discussionmentioning
confidence: 88%
“…Even if the linear relation between the extracted MHD and the INRIA’s model is slighthly better than between the extracted MHD and the proposed model , it has been shown that the proposed method reflects more adequately the reality that the simplified equation proposed by Martin et al (2012). Applying SVD to the extracted MHD clearly shows that this effect is more complex than a simple eigenvector as suggested by Martin et al (2012). This property is important when assessing the quality of a denoising technique for ECG acquired during MRI, since the reduced complexity of the model on INRIA’s model can bias the denoising results when applying dimensionality reduction techniques such as SVD or Independent Component Analysis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The simulation of 12-lead ECG based on partial differential equations (PDE) -as opposed to cellular automata [64] -appeared during the last decade [5,41,50,51,60]. More recently, a focus on the T-wave was proposed [29,34].…”
Section: Introductionmentioning
confidence: 99%